2024
DOI: 10.3390/plants13030463
|View full text |Cite
|
Sign up to set email alerts
|

Increased Accumulation of Ginsenosides in Panax ginseng Sprouts Cultivated with Kelp Fermentates

Kyung-Wuk Park,
Jeong-Ho Kim,
Beom-Gyun Jeong
et al.

Abstract: Currently, new agri-tech has been developed and adapted for the cultivation of crops using smart farming technologies, e.g., plant factories and hydroponics. Kelp (Laminaria japonica), which has a high industrial value, was considered as an alternative to chemicals for its eco-friendly and sustainably wide use in crop cultivation. In this study, a fermented kelp (FK) was developed for use in hydroponics. The FK contained various free and protein-bound amino acid compositions produced by fermenting the kelp wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In addition, cultivation conditions can be precisely controlled without being affected by the external environment, providing uniform, clean, and pesticide-free plants [ 27 , 28 ]. Additionally, the contents of ginsenosides (Rb2, Rb1, Rc, Rd, and Re) in sprout ginseng are increased, as shown in previous studies [ 17 , 18 , 21 ].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, cultivation conditions can be precisely controlled without being affected by the external environment, providing uniform, clean, and pesticide-free plants [ 27 , 28 ]. Additionally, the contents of ginsenosides (Rb2, Rb1, Rc, Rd, and Re) in sprout ginseng are increased, as shown in previous studies [ 17 , 18 , 21 ].…”
Section: Introductionsupporting
confidence: 78%
“…It has the advantage that all roots, stems, and leaves can be consumed. It has also been reported that the content of ginsenosides, the main active ingredients in ginseng, is higher in ginseng sprouts [ 17 , 18 , 21 , 78 ]. Two clinical studies [ 79 , 80 ] reported that ginseng had a good effect on cognitive improvement in AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation